KAJIAN KETERPAKAIAN PENGADAAN BUKU TAHUN ANGGARAN 2010/2011 PERPUSTAKAAN INSTITUT TEKNOLOGI SEPULUH NOPEMBER (ITS) SURABAYA - Marsudiyana Marsudiyana (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2016)
This study was conducted to find out the usability of books acquired by the Library of Sepuluh Nopember Institute Surabaya in 2010/2011. The study analysed data of the books usability, the novelty of the books for citations, and the most frequent publishers. The study used both quantitative and qualitative analysis. The results showed that the usability of the books (both for onsite reading and loan) was 4.04 times/book/5 years. Therefore it concludes that the books were used frequently. Books that were mostly used were the most current collections in three years under the subject of engineering published by Wiley, Cambridge and Pearson.